Análise para o aceite de resíduos para co-processamento em fornos de clínquer - Patricia Monteiro Montenegro (2007)
Co-processing is one of the technologies used in the final destination of industrial waste consisting in thermal destruction at high temperatures at cement kilns, with usage of the energy content and/or of the mineral fraction as raw material. The importance of coprocessing lies in that, by using waste and/or by-products as fuels or raw materials in producing cement, the volume of traditional fossil fuels and traditional raw materials is reduced, as well as the environmental impacts associated to these activities. Nonetheless, activities involved in co-processing may create new risks for the cement industry which must be suitably dealt with. This study consists in developing a risk assessment procedure for the purpose of checking the additional control measures required in helping the decision making process for acceptance of waste products for co-processing, in order to provide for adequate control of these risks. The procedure proposed complies with the Australian Risk Management Standard, focusing on chemical substances involved in the four main impact areas of co-processing, worker health and safety, the environment, product quality and production process, with a view to pointing out risks involved in new or currently coprocessed waste product types, based on the current scenario found in an existing cement plant. The European Waste Catalogue and the European guideline for classification hazardous substances were used for classifying the wastes according to their hazard level . This procedure was applied and validated for the four types of waste product co-processing found in Brazil. Results show that current legal requirements are often generic in nature and in some cases insufficient for the process of acceptance of industrial waste for co-processing in cement kilns in Brazil, making it difficult for cement plant and environmental agency technicians to apply them. Therefore, applying the procedure proposed in this study may help in managing the co-processing risk.